Function Orientation beyond Development – Use Cases in the Late Phases of the Product Life Cycle - Warkentin, A.; Gausemeier, J.; Herbst, J. (Cranfield University Press, 2009)
The importance of a function driven way of working in the field of Electric/Electronic-systems (E/E) is increasing. However, the existing methods are focusing on the development phase. In contrast to this, we performed a comprehensive use case analysis concentrating on the late phases of the product life cycle. In this paper we describe the results of this analysis by illustrating the main use cases identified. For each use case we present a solution of how to exploit potential of function orientation. Based on this we will be able to define a concept of a function-oriented representation.
Organised by: Cranfield University
Keywords: Functions; Function Orientation; Product Life Cycle; Manufacturing Process Planning; Manufacturing